Development and implementation of bottom ash crushing system in Submerged Scrapper Conveyor (SSC) for Coal-fired Power Plant - Basim Ismail, F. (EDP Sciences, 2017)
The existence of Submerged Scrapper Conveyor (SSC) in coal-fired power plant is to handle the by-product of bottom ash. However, soot-blowing will be performed sometimes, in order to remove slag formed at the boiler furnace wall. Thence, this lead to a sudden loading of large amount of slags and bottom ash at SSC after soot-blowing, causing SSC conveying system to jam and conveying chain breakage. In this paper, a new SSC design with additional crushing system is proposed. By implementing the new design proposed, it is expected to improve the overall current performances, and to reduce the trip issue of SSC in coal-fired power plant. The new 3D model of SSC is designed, and stress-strain simulation of the model is analysed by using software of PTC Creo Parametric. Final cost and safety factor analysis of model is made to prove its validation. © The authors, published by EDP Sciences, 2017.